La Biennale di Venezia : Think with the senses, feel with the mind : Art in the present tense : short guide. - Biennale Venetië 2007 (Venezia : La Biennale di Venezia, 2007)
Aballi, Ignasi ; Abd El-Baky, Haiam ; Abdessemed, Adel ; Abidin, Adel ; AES+F Group ; Aghabeyova, Tora ; Ahmed, Fayig ; Al Solh, Mounira ; Alakbarov, Rashad ; Alexiou, Nikos ; Alptekin, Hüseyin ; Alterazioni Video ; Altmejd, David ; Alvarado, Narda Fabiola ; Alys, Francis ; Amer, Ghada ; Anatsui, El ; Anselmo, Giovanni ; Arcidiacono, Dario ; Aslanov, Orkhan ; Babayev, Chingiz T. ; Bajic, Mrdjan ; Balassanian, Sonia ; Bamgboyé, Oladélé ; Barcelo, Miguel ; Barrada, Yto ; Bartenev, Andrei ; Basilico, Gabriele ; Basquiat, Jean-Michel ; Bengoa, Monica ; Benjamin, Mario ; Bidjocka, Bili ; de Boer, Manon ; Bombardieri, Stefano ; Bouabdellah, Zoulikha ; Bourgeois, Louise ; Brandl, Herbert ; Bratkov, Sergey ; Braun, Jan Christiaan ; Briceño, Antonio ; Bueno, Patricia ; Buren, Daniel ; buvoli, luca ; Byrne, Gerard ; Caldas, Waltercio ; Calle, Sophie ; Canevari, Paolo ; Capurro, Christian ; Cardoso, Pablo ; Castellanos, Mariadolores ; Chen Zhen ; Cherinet, Loulou ; Chkadua, Eteri ; Chusuwan, Amrit ; Cybil, Vladimir ; Dahdouh, Bassem ; Dahlgren, Jacob ; Damasceno, José ; Dergham, Sahar ; Detanico, Angela ; Drake, James ; Dumas, Marlene ; Duyckaerts, Eric ; Dyu, Natalya ; Dzine ; Effendi, Rena ; Eielson, Jorge ; El-Koumy, Tarek ; El-Semary, Aiman ; Elkoury, Fouad ; Emin, Tracey ; Epaminonda, Haris ; de Espirito Santo, Iran ; Export, Valie ; Eyfjörd, Steingrimur ; Fatmi, Mounir ; Fei, Cao ; Ferrari, León ; Ferreira, Angela ; Fikry, George ; Filomeno, Angelo ; Fischer, Urs ; Fogarasi, Andreas ; Francisco, René ; Frangulyan, Georgy ; Franke, Ivana ; Fudong Yang ; Fujimoto, Yukio ; Gabrans, Gints ; Gaines, Charles ; Ganahl, Rainer ; Ganihar, Tomer ; Garcia Torres, Mario ; Geers, Kendell ; Genzken, Isa ; Gjergji, Helidon ; Gjokola, Genti ; Gladwell, Shaun ; etc.
La Biennale di Venezia 2007, Venetië, 2007-06-10 tot 2007-11-21
boek